Telling-Writing Technique as Psychological and Literacy Therapy for Children Affected by the Covid-19 Pandemic Disaster - Nisa Roiyasa; Prayogo Hadi Sulistio (Journal of Nonformal Education, 2023)
Negative and permanent impacts of Covid-19 pandemic and distant learning are can be serious and permanent to students at the Primary School level. This is a dangerous threat considering that elementary school is a time of instillation of basic values, skills, and knowledge for the physical, cognitive, and affective development. Researchers conducted a research in Lumbir district, Banyumas regency and designed a technique for psychological and literacy therapy for children in elementary school age affected by the Covid-19 pandemic. This research is an experimental study. The findings are served in qualitative descriptive way. The research revelas that Children's Mental Health should be the main focus in the early days of learning. Just above a half of the students in Lumbir as border area do not live with their parents as their parents must work in big cities. There were significant changes on mental, behavior and one-year learning loss due to the pandemic. The technique is proven able to eliminate affective filters on the students affected by covid-19 pandemic.